(untitled) (Revista de Investigaciones Universidad del Quindío, 2009)
In this paper we show some preliminary results of the liquid phase epitaxy growth process for the heterostructures GaSb/GaInAsSb/GaSb. We describe the fabrication process of the heterostructures and also we present the analysis of its X-Ray Diffraction patterns (XRD) and Photoluminescence (PL) characterization. These results evidenced the epitaxial growth of the heterostructures.